2019
DOI: 10.1002/pbc.27740
|View full text |Cite
|
Sign up to set email alerts
|

Greater number of perceived barriers to hydroxyurea associated with poorer health‐related quality of life in youth with sickle cell disease

Abstract: Background: Despite medical benefits, hydroxyurea adherence in adolescents is often poor. As part of a baseline assessment of 28 youth (10–18 years) parent dyads who participated in a 6-month feasibility trial to improve hydroxyurea adherence, we measured the relationship between greater barriers to adherence and health-related quality of life (HRQL) from youth and parent perspectives. Procedure: Barriers were measured using the Adolescent and Parent Medication Barriers Scales with nine hydroxyurea items add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 62 publications
0
29
1
1
Order By: Relevance
“…Some of the studies on barriers to adherence showed a correlation between the number of barriers and medication adherence, a finding we did not observe in our cohort. 50,51 Our inability to detect statistically significant correlation is likely related to our inadequate power from our small sample size. However, assessing for the common barriers and those correlated with adherence in routine clinical practice can provide insight to promote individual patient adherence level.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some of the studies on barriers to adherence showed a correlation between the number of barriers and medication adherence, a finding we did not observe in our cohort. 50,51 Our inability to detect statistically significant correlation is likely related to our inadequate power from our small sample size. However, assessing for the common barriers and those correlated with adherence in routine clinical practice can provide insight to promote individual patient adherence level.…”
Section: Discussionmentioning
confidence: 91%
“…50 Using ≥25% as a cutoff for reporting barriers as common, previous work in sickle cell disease found six common barriers for parents and 12 common barriers in adolescent patients. 50 In our study, 12 barriers met criteria for being common in parents and ten barriers were common in adolescents, which highlights the complexity of taking oral chemotherapy even for parents. The variety of barriers emphasizes the need for tailored multifaceted or multifunctional interventions to promote adherence behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Details regarding conduct of the HABIT trial and its results have been reported elsewhere (Green et al, 2017; Smaldone et al, 2016; Smaldone et al, 2018; Smaldone et al, 2019). Data from the baseline assessment of these subjects were used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Using 2005-2012 Medicaid data from six states, findings of a recent study suggest that less than 20% of youth for whom HU was prescribed received at least 300 days of medication [89]. Barriers to HU are pervasive and may differ for parents and youth [28]. This points to the critical need for interventions to improve adherence for these vulnerable youth.…”
Section: Discussionmentioning
confidence: 99%
“…Poor adherence is linked to inadequate integration of adherence into a daily medication habit [23]. Barriers to medication adherence are common in youth with chronic illness [15, 2428] and a source of racial/ethnic disparities in underserved communities [29]. Poor medication adherence increases disease burden, healthcare cost and widens health disparities [30, 31].…”
Section: Introductionmentioning
confidence: 99%